Effect of a Fibroblast Growth Factor, Insulin, Dexamethasone, and Serum on the Morphology of BALB/c 3T3 Cells - Gospodarowicz, Denis (1974)
The effects of serum, fibroblast growth factor, dexamethasone, and insulin on the morphology of two lines of BALB/c 3T3 cells are described and illustrated. Fibroblast growth factor, a polypeptide purified from bovine brain and pituitary glands, stimulates DNA synthesis and cell division in both sparse and confluent cultures of quiescent 3T3 cells. When cells are grown in the presence of the factor, they go through one or two cycles of division and their morphology differs from that of cells either growing in 10% serum or maintained in a quiescent state in low serum; they appear rounded with long processes and show no sign of contact inhibition. When dexamethasone is present with the growth factor, the cells grow to a high density and are not contact-inhibited; they have the appearance of transformed cells. Addition of insulin or dibutyryl cyclic AMP to the cells results in a morphology similar to that of cells growing in the presence of serum. Addition of growth factor or growth factor plus dexamethasone to cells that have reached confluency in 10% serum and that are clearly contact-inhibited results in the resumption of growth. The final cell density reached is similar to that of cells growing in the presence of 30% serum with daily fluid changes. No contact inhibition is observed in either of these situations.